Assessment of a Chemical Formulation for Acrylic Matt and Acrylic Gloss Paints - Hebah Abdel-Wahab; Tamara Gund (Research Aspects in Chemical and Materials Sciences Vol. 3, 2022)
Paints are used to prolong the life of natural and synthetic materials and to protect it, it acts as a barrier against environmental conditions. Mainly paints are made up of solvent, biner, extenders, pigments(s), and some additives. The goal is to identify the chemical compounds and the literature amounts that constitute a good acrylic paint, as well as chemicals that could potentially reduce scrub resistance and additives and chemical compounds that could potentially improve the quality and scrub resistance test for acrylic paints. It has been determined that three key chemical compounds—pigments, extenders, and another kind of pre-emulsion monomer—are absent from the current formulation after researching the chemical characteristics and functions of each chemical compound used in it and comparing the amounts used to reference values. It has also been discovered that the current formulation’s low scrub resistance test results compared to the reference are due to the abundance of surfactants, specifically 4.5 percent (2.0 percent Octyl phenol Polyglycol Ether Sulfate Sodium Salt, 2.0 percent Octyl phenol Polyglycol Ether Sulfate Sodium Salt, and 0.5 percent Provichem).